Assessment of the Election Manifestos of Uzbekistan Political Parties Between 2019-2024 - Halil Emre Deniş (İmgelem)
Election manifestos are important policy documents for political parties. These documents are published before the election periods and are an important observation document for the evaluation of the promises and policies of political parties in the post-election period. In line with these documents, voters can track whether the promises made are fulfilled or not. These declarations include certain issues. Generally, these issues consist of areas where policy will be produced continuously in democratic societies. Accordingly, the election declarations prepared by the political parties of Uzbekistan for the period between 2019-2024 were examined. The discourses of each political party on the economy, judiciary, health, education and foreign policy, which are common in their election manifesto, were examined. This study aims to determine the similarities and differences in the common issues determined in the election manifestos of the political parties of Uzbekistan.